A new default restraint library for the protein backbone inPhenix Phenix: a conformation‐dependent geometry goes mainstream. Issue 1 (1st January 2016) - Moriarty, Nigel W.; Tronrud, Dale E.; Adams, Paul D.; Karplus, P. Andrew
Abstract : The default geometry restraints used in Phenix Phenix for the protein backbone have been upgraded to account for the known conformation‐dependencies of bond angles and lengths. Abstract : Chemical restraints are a fundamental part of crystallographic protein structure refinement. In response to mounting evidence that conventional restraints have shortcomings, it has previously been documented that using backbone restraints that depend on the protein backbone conformation helps to address these shortcomings and improves the performance of refinements [Moriarty et al. et al. (2014), FEBS J. FEBS J. 281 281, 4061–4071]. It is important that these improvements be made available to all in the protein crystallography community. Toward this end, a change in the default geometry library used by Phenix Phenix is described here. Tests are presented showing that this change will not generate increased numbers of outliers during validation, or deposition in the Protein Data Bank, during the transition period in which some validation tools still use the conventional restraint libraries.